The Effectiveness Of Scientific Approach With Open-Ended Problem Based Learning Worksheet Viewed From Learning Achievement, Creative Thinking Ability, Interest, And Mathematics Self-Efficacy - Lisda Fitriana Masitoh; Enggar Prasetyawan (Universitas Negeri Makassar, 2019)
This study aimed to describe the effectiveness and differences of scientific approach with open-ended problem based learning worksheet and scientific approach. The population in this study was students of class VII of SMP Negeri 17 Pamulang, South Tangerang. The sample of this study was determined randomly. They were two classes and the results were VII.3 and VII.4. To determine the effectiveness, one sample t-test was used. To discover the difference of effectiveness, MANOVA (Hotteling's Trace) test was used. The results show that (1) Scientific approach with open-ended problem based learning worksheet and scientific approach are effective viewed from learning achievement, creative thinking ability, interests and mathematic self-efficacy (2) There is no difference in effectiveness between scientific approach with open-ended problem based learning worksheet with scientific approach viewed from learning achievement, creative thinking ability, interests and mathematic self-efficacy (3) Scientific approach with open-ended problem based learning worksheet are more effective than scientific approaches viewed from student achievement